PKM Media Digital 3D Bagi Guru Ekonomi - Syamsu Rijal; Andi Caezar To Tadampali; Andi Tenri Ampa; Ratna, S; Andi Annisa Sulolipu (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Interesting learning must be supported by the use of interesting media, of course integrated with the use of technology, information and communication so that teachers can develop their digital literacy potential. Through information technology networks, teachers can create teaching materials practically and easily. The application of technology-based media products in learning in schools has a positive impact on student learning outcomes. Student learning outcomes are better when compared to learning without using technology. Technology network devices have helped teachers design digital-based teaching materials. In order to improve teachers' abilities in compiling digital modules, 3D digital media training is needed to create modules using the Canva application. The methods used in this study include lectures, questions and answers or discussions, and training. The results obtained are (1) The implementation of 3D digital media training activities for economics teachers focuses on training on how to create 3D digital media that can be used as learning tools in the teaching and learning process and are able to apply them in teacher activities, (2) The implementation of activities can run smoothly according to the previously prepared plan, and (3) Participants in the activity are greatly helped by this activity because participants gain additional knowledge about creating 3D digital media.